Margin dan Pangsa Pasar Rajungan Portunus pelagicus (Linnaeus, 1978) di Wilayah Pesisir Timur Lampung - Yuwana Utami Cendrakasih; Indra Gumay Yudha; Indra Gumay Febryano; Erna Rochana; Supono Supono; Thomas Nugroho; Muhamad Karim (Universitas Bangka Belitung, 2023)
The market and market share has an important role for business actors (fishermen and crab processors) in their economic, social, and institutional activities. This study aimed to analyze the margin and price share of crab trade at each trading agency involved. Data collection is done by interviews using questionnaires, literature studies, and data from government and private agencies. All data collected were analyzed used the description method to determine the margin and market share of the crab. The results showed that the margins of the crab trading varied between levels of trading agency, i.e fishermen (Rp34,500.00- 50,200.00), small collectors (Rp5,000.00-15,000.00), middleman (Rp35,000.00-60,000.00), miniplant (Rp27,500-125,676.00), and UPI (Rp901,511.00-971,511.00). Fisherman's share value also varied between 16.43-22.97. Overall from fishery export commodities in Lampung Province, crab ranked second seafood product (after shrimp) with a market share of 19.76% and most of it (92.67%) with volume 1.070.237 kg was exported to the United States as pasteurized crab meat. Crab trading agency involved are expected to prioritize the quality and quantity of products so that the margin and market share of the crab will increase